RECONSTRUCTING RELIGIOUS TOLERANCE: A LOCAL WISDOM APPROACH AFTER TERROR ACTS IN INDONESIA'S MULTICULTURAL SOCIETY - Mukari, M; Anas, Moh. (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This research aims to explore the role of local wisdom in the reconstruction of religious tolerance after acts of terror in Indonesia. Acts of terrorism not only cause physical casualties, but also damage interfaith social relations that were previously established. In this context, tolerance reconstruction becomes an urgent need to restore fragile social trust. The approach offered is the utilization of local wisdom, which has historically proven to play a role as a unifying instrument for Indonesia's multicultural society. This research uses a narrative review design by examining 25 relevant national and international journal articles. The articles reviewed cover issues of tolerance, post-conflict reconciliation, multicultural education, and the role of local traditions in strengthening social cohesion. Analysis was conducted using thematic-narrative method to identify patterns, strategies, and mechanisms of local culture-based reconciliation. The synthesis results show that local wisdom, such as the tradition of Torang Samua Basudara in Minahasa, Ngejot in Lombok, as well as other cultural practices such as oral literature and customary deliberation forums, play a significant role in rebuilding interfaith relations. The integration of universal religious values with local culture strengthens social mechanisms in restoring interfaith trust. In addition, strategies based on multicultural education, cultural communication, and community reconciliation proved effective in creating space for dialogue and strengthening social solidarity after extreme violence. This study concludes that the reconstruction of post-terror religious tolerance must prioritize a local wisdom-based approach, combined with education and religious values. The research contribution lies in offering a new framework that is more contextual, operational, and relevant than the global normative approach. The findings also open up opportunities for broader follow-up research related to the implementation of local wisdom-based reconstruction models in various regions of Indonesia.